2022
DOI: 10.1136/heartjnl-2022-321167
|View full text |Cite
|
Sign up to set email alerts
|

Salt restriction and risk of adverse outcomes in heart failure with preserved ejection fraction

Abstract: BackgroundThe optimal salt restriction in patients with heart failure (HF), especially patients with heart failure with preserved ejection fraction (HFpEF), remains controversial.ObjectiveTo investigate the associations of cooking salt restriction with risks of clinical outcomes in patients with HFpEF.MethodsCox proportional hazards model and subdistribution hazards model were used in this secondary analysis in 1713 participants with HFpEF from the Americas in the TOPCAT trial. Cooking salt score was the sum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Low sodium intakes could lead to AF through orthostatic hypotension 33,34 and activation of the renin-angiotensin-aldosterone system, as well as increased adrenaline excretion. 35,36 Besides observational studies that have reported J-or U-shaped associations between sodium intake and cardiovascular outcomes, 8,10,[12][13][14][15][16][17][18] there are also data from interventional studies, 37 including a recent meta-analysis showing an increased risk of in-hospital death in patients with heart failure on sodium-restricted diets in clinical trials 38 and data showing an inverse correlation between country-level sodium intake and life expectancy. 39 Despite this, current guidelines recommend lowering sodium intake to a goal of between less than 1.50 g/d to less than 2.40 g/d.…”
Section: Discussionmentioning
confidence: 99%
“…Low sodium intakes could lead to AF through orthostatic hypotension 33,34 and activation of the renin-angiotensin-aldosterone system, as well as increased adrenaline excretion. 35,36 Besides observational studies that have reported J-or U-shaped associations between sodium intake and cardiovascular outcomes, 8,10,[12][13][14][15][16][17][18] there are also data from interventional studies, 37 including a recent meta-analysis showing an increased risk of in-hospital death in patients with heart failure on sodium-restricted diets in clinical trials 38 and data showing an inverse correlation between country-level sodium intake and life expectancy. 39 Despite this, current guidelines recommend lowering sodium intake to a goal of between less than 1.50 g/d to less than 2.40 g/d.…”
Section: Discussionmentioning
confidence: 99%
“…Where ejection fraction was not recorded in the medical record, from the current admission, this data was obtained from the patient's prior admissions. Patients admitted with heart failure with preserved ejection fraction (HFpEF) were excluded due to inadequate evidence for the benefits of restricting sodium intake [13,14]. Additionally, due to research previously undertaken in the intensive care unit (ICU), days in which patients were in ICU were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…However, contrary to expectation, a recent study in patients with HFpEF revealed that an exaggerated dietary salt restriction could harm patients with HFpEF and is associated with a worse prognosis. 22 Machado et al also found that aggressive salt/water restriction does not provide clinical benefits in patients with HFpEF. 23 A lack of uniformity in limiting the amount of sodium restriction per day, unclear data on the associated use of fluid restriction, and simultaneous usage of diuretics and neurohormonal blockade agents as well as heterogeneity of the HF population studied could provide an explanation for the conflicting evidence in the HFpEF subset.…”
Section: Sodium Restriction In Hfpefmentioning
confidence: 99%
“…However, contrary to expectation, a recent study in patients with HFpEF revealed that an exaggerated dietary salt restriction could harm patients with HFpEF and is associated with a worse prognosis. 22 Machado et al also found that aggressive salt/water restriction does not provide clinical benefits in patients with HFpEF. 23…”
Section: Salt and Heart Failurementioning
confidence: 99%